2012
DOI: 10.1021/jp207271p
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Thermochemical Properties of Amino Acids: Gas-Phase and Aqueous Acidities and Gas-Phase Heats of Formation

Abstract: The gas-phase acidities of the 20 L-amino acids have been predicted at the composite G3(MP2) level. A broad range of structures of the neutral and anion were studied to determine the lowest energy conformer. Excellent agreement is found with the available experimental gas-phase deprotonation enthalpies, and the calculated values are within experimental error. We predict that tyrosine is deprotonated at the CO(2)H site. Cysteine is predicted to be deprotonated at the SH but the proton on the CO(2)H is shared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
114
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(137 citation statements)
references
References 86 publications
18
114
2
3
Order By: Relevance
“…Cysteine has been investigated theoretically and experimentally and has been found to form a thiolate ion by side chain deprotonation with a strong hydrogen bond to it from the carboxylate group. 1,21,22 In addition, Ren and co-workers have observed cysteine side chain deprotonation in experimental and computational GA studies of small cysteine-containing peptide amides. 23−26 These studies indicate that residue side chains may deprotonate in the gas phase even in the absence of a side chain carboxylic acid group.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cysteine has been investigated theoretically and experimentally and has been found to form a thiolate ion by side chain deprotonation with a strong hydrogen bond to it from the carboxylate group. 1,21,22 In addition, Ren and co-workers have observed cysteine side chain deprotonation in experimental and computational GA studies of small cysteine-containing peptide amides. 23−26 These studies indicate that residue side chains may deprotonate in the gas phase even in the absence of a side chain carboxylic acid group.…”
Section: ■ Introductionmentioning
confidence: 99%
“…An amino acid's behavior in biological systems depends in part on their fundamental chemical properties, including their intrinsic acid/base properties [1]. Solution pK a values for all of the common protein amino acids (PAA) are readily available [1], as are the intrinsic gasphase proton affinities (PA) and gas-phase acidities (GA, DH acid ) [19,22,23,[25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…A range of structures were optimized to determine the most stable conformers. In our previous work on amino acid acidities [35][36][37] [and Bokatzian-Johnson, S. S.; Stover, M. L.; Dixon, D. A.; Cassady, C. J., unpublished results] we showed that the high level G3(MP2) correlated molecular orbital method [38] gave agreement for the acidities with the experimental values to within about ±1 kcal/mol. G3(MP2) has an additional advantage over DFT methods in terms of reliable predictions for these types of compounds because the correlated molecular orbital methods in G3(MP2) perform better in the prediction of hydrogen bond energies as well as steric non-bonded interactions than do most widely-used DFT exchange-correlation functionals.…”
Section: Computationsmentioning
confidence: 54%
“…Elimination of valine has also been observed by Jai-nhuknan [91] in a study of protonated transform growth factor (TGF) α [34][35][36][37][38][39][40][41][42][43] 3+ from TGF α (34−43), which has a C-terminal carboxylic acid group and a disulfide bond [91]. Jai-nhuknan [91] also studied the reduced form of TGF α [34][35][36][37][38][39][40][41][42][43], where the disulfide bond is cleaved; this ion did not eliminate the valine residue. This suggests that the intact disulfide bond in TGF α [34][35][36][37][38][39][40][41][42][43] facilitates a peptide ion conformation that contributes to a unique loss of an internal valine residue [91].…”
Section: Internal Valine Residue Lossmentioning
confidence: 89%
See 1 more Smart Citation